Multicenter epidemiological study of maxillofacial trauma: a one-year retrospective-descriptive assessment of 1356 cases in a Colombian metropolitan region - Jessica Lozano-Pérez; Sandra Jaramillo-Monroy; Gustavo Ortiz-Orrego; Verónica Gómez-Arcila; Sara Arias-Mendieta; Sergio Tobón-Arroyave (Journal of Oral Research, 2021)
Background: This retrospective study was conducted to identify the epidemiological profile and treatment modalities linked to the maxillofacial trauma (MFT) managed in the Maxillofacial Surgery Departments of seven hospital centers in Antioquia, Colombia. Material and Methods: Clinical records with specific attention to sociodemographic characteristics, mechanisms of injury, type of MFT, location of injuries, and treatment modalities of MFT were collected from January to December 2017. Descriptive analyses using Pearson's chi-square tests were performed. Results: A total of 1356 records were retrieved. Males were significantly more affected, with a male-to-female ratio of 3.85:1. The most susceptible age group involved was young adults (18 to 40 years). A low percentage of alcohol (9.3%) and drugs consumption (2.5%) was recorded. Most common causes of MFT were road traffic accidents (RTA), falls, and interpersonal violence (IPV). Most injuries involved both soft and hard tissues, followed by hard tissues and isolated open soft tissue injuries. Among fractures, the middle third was the most commonly affected site and the utmost method of treatment was open reduction and internal fixation. Conclusion: Within the limitations of the evidence available, this study has demonstrated that the gender, age stratum, and etiological factors, such as RTA, falls, and IPV, but no alcohol and/or psychoactive substances' consumption, may have a significant influence on the prevalence, patterns, and treatment modalities of MFT in this sample population.